PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI PT LINTAS TIMUR SEJAHTERA JAKARTA UTARA - Roy Irawan; Darma Wijaya; Intan Kusuma Dewi; Indra Prana; Natasya Marti (Jurnal Akrab Juara, 2019)
Service quality is closely related to customer satisfaction. Customer satisfaction can be achieved if customers get services that are in line with what is needed and expected. PT Lintas Timur Sejahtera North Jakarta is a company engaged in freight forwarding services. To maintain and increase customer satisfaction every item is sent immediately so that it is timely to the destination for customer satisfaction. Thus the expected service quality that has been given has an effect on increasing customer satisfaction. To determine the effect of service quality on customer satisfaction at PT Lintas Timur Sejahtera, North Jakarta, the authors conducted a Quantitative method. How to get Observation, Interview, Questionnaire data with valid and reliable conditions and Documentation Study. Based on the results of the Correlation Coefficient Test between the Quality of Service and Customer Satisfaction gives a coefficient of 0.831 it can be concluded that the relationship between Service Quality and Customer Satisfaction is very strong. Based on the results of the Determination Coefficient, the percentage of contribution to the influence of Service Quality variable on Customer Satisfaction 69%. Based on the Regression Equation Test obtained by value t count> t table (7,907> 2,048) and significance <0,05 (0,000 <0,05), it can be concluded that Service Quality influences Customer Satisfaction.